2002
DOI: 10.1111/j.0004-8666.2002.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes versus obesity as risk factors for pregnancy‐induced hypertensive disorders and fetal macrosomia

Abstract: Our data strongly suggest that GDM and obesity are not independent risk factors for pregnancy-induced hypertensive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 15 publications
(8 reference statements)
5
22
1
Order By: Relevance
“…This finding has been observed by others as well (25,26) and suggests an underlying vascular pathology that might predate pregnancy and result in abnormal placentation (27), leading to placental hypoperfusion and the release of circulating compounds able to alter the maternal vascular endothelium (28).…”
Section: Postpartum Testingsupporting
confidence: 72%
See 1 more Smart Citation
“…This finding has been observed by others as well (25,26) and suggests an underlying vascular pathology that might predate pregnancy and result in abnormal placentation (27), leading to placental hypoperfusion and the release of circulating compounds able to alter the maternal vascular endothelium (28).…”
Section: Postpartum Testingsupporting
confidence: 72%
“…Roberts et al (24) studied 11 women with preeclampsia and 11 nonpreeclamptic control subjects in the third trimester using the minimal model technique and found no differences between the groups. In a retrospective review, Van Hoorn et al (25) found no difference in preeclampsia rates in women with GDM (19.6%, n ϭ 51) compared with control subjects (17.1%, n ϭ 258). They also report that the preeclamptic women were taller (by 1.9 cm; P Ͻ 0.05) and had higher DBP at booking (P Ͻ 0.001) than the control subjects.…”
Section: Postpartum Testingmentioning
confidence: 97%
“…Glucose tolerance status, and especially obesity, acted in a dose-dependent manner, increasing the risk of perinatal complications as glucose intolerance and BMI increased. Glucose intolerance or obesity was not significantly associated with PIH or macrosomia in an Australian cohort [22]. The present study, partially reported in [15], identifies pregestational BMI and abnormal glucose tolerance categories as independent predictors of perinatal outcome with similar ORs for abnormal glucose tolerance categories and upper BMI quartiles.…”
Section: Discussionsupporting
confidence: 53%
“…However, few studies have attempted to discern the relative influences of overweight and GDM [22][23][24][25][26][27]. Obesity and hyperglycaemia have been reported to be independent predictors of different obstetric and perinatal complications, but obesity was a stronger risk factor for macrosomia, Caesarean section and hypertension than hyperglycaemia [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists as to whether pregravid obesity alone, GDM, hyperglycemia, and treatment modality are independent risk factors for adverse pregnancy outcome. The majority of studies have not controlled for obesity, parity, or level of glycemic control, and in many studies, sample sizes were too small to allow sufficient statistical power (57)(58)(59)(60)(61)(62). Recently, in a prospective study on 4,001 GDM patients (63), it was shown that obese and overweight GDM patients achieving established levels of glucose control with insulin therapy showed no increased risk for composite adverse outcomes, macrosomia, and LGA in comparison to normal-weight GDM patients with good control.…”
Section: Level Of Glycemia and Fetal Metabolicmentioning
confidence: 99%